2022
DOI: 10.1016/j.molstruc.2021.131482
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of a cationic antimicrobial peptide into self-assembled polyion complex nano-objects enhances its antitumor properties

Abstract: Antimicrobial peptides, a large class of molecules synthetized by various organisms as an innate defense against pathogens are more and more used for their anticancer properties as well. In order to overcome some of their limitations and to enhance their therapeutic efficiency, the use of delivery systems was taken into consideration. In this study we describe an original delivery system for antimicrobial peptides based on its physico-chemical properties, namely the selfassembled polyion complexes (PIC) based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The tumor spheroid model can be used in testing new chemotherapeutic agents; however, to our knowledge, there are only a limited number of studies reporting on antitumor peptides [ 17 , 45 , 46 , 47 ]. A recent study by Hadianamrei and collaborators has reported on the anticancer activity of short cationic a-helical peptides against both HCT-116 cells grown in a monolayer or spheroids [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor spheroid model can be used in testing new chemotherapeutic agents; however, to our knowledge, there are only a limited number of studies reporting on antitumor peptides [ 17 , 45 , 46 , 47 ]. A recent study by Hadianamrei and collaborators has reported on the anticancer activity of short cationic a-helical peptides against both HCT-116 cells grown in a monolayer or spheroids [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four of the peptides had reduced toxicity against human dermal fibroblasts, which indicated that the use of lysine residues instead of arginine ones would reduce the cytotoxic effect on normal cells [ 45 ]. We also reported previously the antitumor activity of one known AMP, Gramicidin A [ 17 ], and a new synthetized peptide, P6 [ 46 ], with improved activity against HT-29 and HCT-116 spheroids, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, the neutral block that provides colloidal stability through steric repulsion is poly­(ethylene oxide) (PEO), ,,, but sometimes other polymer blocks are used, such as poly­(vinyl alcohol) (PVA) or poly­(acrylamide) (PAAm), to name a few. Previously, other proteins, drugs, and peptides, e.g., (helical) polypeptides, , doxorubicin, lysozyme, , myoglobin, bovine serum albumin (BSA), and many others have been successfully complexed into C3Ms. ,,,, In contrast, complex coacervation involving AMPs is limited to a few studies. ,, The AMPs polymyxin B, colistin, temporin-L, KSL-W, P6, and MSI-78 have successfully been complexed into coacervates, with only the latter two into C3Ms, which are generally recognized for their enhanced stability compared to typical coacervates . Răileanu et al complexed P6 with PEO- b -poly­(acrylic acid) (PAA), while Wang et al prepared C3Ms from the complexation of MSI-78 with methoxyPEO- b -poly­(α-glutamic acid) (PGlu) .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, other proteins, drugs, and peptides, e.g., (helical) polypeptides, , doxorubicin, lysozyme, , myoglobin, bovine serum albumin (BSA), and many others have been successfully complexed into C3Ms. ,,,, In contrast, complex coacervation involving AMPs is limited to a few studies. ,, The AMPs polymyxin B, colistin, temporin-L, KSL-W, P6, and MSI-78 have successfully been complexed into coacervates, with only the latter two into C3Ms, which are generally recognized for their enhanced stability compared to typical coacervates . Răileanu et al complexed P6 with PEO- b -poly­(acrylic acid) (PAA), while Wang et al prepared C3Ms from the complexation of MSI-78 with methoxyPEO- b -poly­(α-glutamic acid) (PGlu) . As shown by these examples, in combination with the limited research on the detailed structural investigation of the AMP complexes, the complexation of AMPs is still widely unexplored, even though this structural analysis is potentially highly relevant in the development of new antibiotic formulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation